"ein rise starc unde grôz": Geographies and temporalities of salvation in St. Jakob in Kastelaz. Issue 4 (2nd October 2019) - Pinkus, Assaf
Abstract: A pair of naked giants, male and female, gazing toward the congregation, flank the apse of St. Jakob in Kastelaz ( c .1215) in Tramin, South Tyrol. This article argues that, rather than portraying specific giants from a particular text, the mural figures embody the notion of "the gigantic" as it appears in contemporary medieval epics, romances, and travel literature. As such, they confront viewers with a variety of geographies and temporalities of salvation, connecting the Flood and its redemptive implications to a broad spectrum of mythical times, sacred history, and cosmology, as well as to a wide range of locations across the globe, both near and far. Amid this rich cultural web, the giants in the frescoes offer their viewers two types of pictorial vision: a false one, represented by the hybrids struggling in the obliterating deluge; and a true vision of the Majestas Domini and the Apostles, attainable by humanity alone.